Valuasi Nilai Relatif dan Intrinsik Saham Sektor Petrokimia - Utama, Yusuf Ammar; Anwar, Mokhamad (Jurnal EMT KITA, 2025)
This study was conducted to determine the results of the valuation analysis of petrochemical sector stocks in Indonesia using the intrinsic value valuation method and relative valuation by comparing market prices. The research method used to conduct valuation is the intrinsic value approach using Discounted Cash Flow (DCF) with the Discounted Cash Flow (FCFF) model and relative value using the Price to Earnings (P/E), Price to Sales (P/S), and Price to Book Value (PBV) ratios. The sampling technique in this study is Purposive Sampling in accordance with predetermined criteria, namely petrochemical sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2023. Stock analysis is carried out using the Top-Down Approach, starting with macroeconomic analysis, industry analysis using Porter's Five Forces, and company analysis using financial ratios. The results of intrinsic and relative value valuation that petrochemical sector stocks there are four companies that are considered overvalued, namely, BRPT, TPIA, FPNI, and ADMG. UNIC is the only one that is undervalued with an intrinsic value above the market price. So it is recommended to buy UNIC shares and sell BRPT, TPIA, FPNI, and ADMG.